Demand Response for Integrating Distributed Energy Resources in Transactive Energy System. (February 2019) - Li, Biao; Wan, Can; Yuan, Kai; Song, Yi
Abstract: Transactive energy system (TES) is a system of economic and control mechanisms showing high ability to integrate distributed energy resources (DERs). This paper introduces a market-based demand response strategy to integrate DERs into the retail market using transactive energy framework. A retail market pricing model is proposed for retailer to maximize his profits taking net load fluctuations and grid price waving into account. An operating model is established for end-users to adjust their controllable load or storage to accommodate to the price waving in the retail market. Case studies show that the transactive between retail market and end-users is contributed to reducing the peak-to-valley difference in grid load, integrating DERs and facilitating a win-win situation for both parties.